Mushroom ( Amanita phalloides) Poisoning: Mechanisms, Pathogenesis, Prognosis and Strategies of Treatment - Afrah Thiab Hlail (University of Thi-Qar Journal of Science, 2021)
Poisoning due to mushroom consumption is uncommon, but it causes death by causing acute liver failure (ALF). The ingestion of Amanita phalloides, is one of the ultimate frequent causes of mushroom poisoning globally. This type has three main categories of toxins: amatoxins, phallotoxins, and virotoxins. From these toxins amatoxins and its metabolite α-amanitin, is the main cause of toxicity in population which cause deterioration in synthesis of protein and consequent cell necrosis and inhibition of RNA polymerase II ,so finally cause cell death. Liver is the chief organ involved in toxicity, kidneys and central nervous system also involved. Latent period has been proceeds the poisoning symptoms, which includes gastrointestinal symptoms followed by liver failure symptoms, coma and ultimately death. Management including supportive cares, gastrointestinal decontamination, special medications (Benzyl penicillin, N-acetyl cyctien, cimetidine, silibinin and others) and, finally liver transplantation if clinical condition deteriorated.